2022
DOI: 10.1186/s12877-022-03525-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory potential and the probable sarcopenia among community-dwelling older adults: a cross-sectional study

Abstract: Background Unlike the numerous studies concerning the role of dietary inflammatory potential in chronic diseases, limited studies focused on the association of dietary inflammatory potential with handgrip strength (HGS) and probable sarcopenia (PS). This study tends to explore the association between dietary inflammatory potential and PS among older adults in Tehran. Methods The cross-sectional study was conducted between May and October 2019 on 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…First, legumes, nuts, and vegetable oils are rich in unsaturated fatty acids such as alpha-linolenic acid (ALA) and other nutrients that may help reduce plasma inflammatory cytokine levels and improve muscle inflammation associated with aging, thereby protecting muscle mass in older adults [ 26 , 27 ]. A cross-sectional study also suggested that participants who adhered to a pro-inflammatory diet were more likely to develop sarcopenia [ 28 ]. In addition, vegetables and fruits are rich in nutrients, including polyphenols, antioxidant vitamins and plant proteins that reduce oxidative stress in muscles and positively result in mitochondrial modifications [ 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, legumes, nuts, and vegetable oils are rich in unsaturated fatty acids such as alpha-linolenic acid (ALA) and other nutrients that may help reduce plasma inflammatory cytokine levels and improve muscle inflammation associated with aging, thereby protecting muscle mass in older adults [ 26 , 27 ]. A cross-sectional study also suggested that participants who adhered to a pro-inflammatory diet were more likely to develop sarcopenia [ 28 ]. In addition, vegetables and fruits are rich in nutrients, including polyphenols, antioxidant vitamins and plant proteins that reduce oxidative stress in muscles and positively result in mitochondrial modifications [ 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to confirm that a pro-inflammatory diet may increase the risk of non-communicable diseases, such as obesity, diabetes, cancer, cardiovascular disease, and adverse mental health outcomes [ 13 , 14 ]. Additionally, several studies have found that pro-inflammatory diets are associated with a decline in muscle mass and function [ 15 - 17 ]. However, different diagnostic criteria are used to identify sarcopenia across populations, countries, and regions, while different dietary patterns and cultural backgrounds also affect its prevalence.…”
Section: Introductionmentioning
confidence: 99%